2012
DOI: 10.1515/bmt-2012-4481
|View full text |Cite
|
Sign up to set email alerts
|

Damping of the dynamic pressure amplitude in the ventilatory circuit during high-frequency oscillatory ventilation

Abstract: The study deals with experimental measuring of attenuation of dynamic pressure during high-frequency oscillatory ventilation. The experimental circuit consists of high-frequency oscillatory ventilator Sensormedics 3100 B, patient circuit and lung model 5600i. Different values of the flow resistance and alveolar compliance were modelled during the experimental measurement. The ventilatory parameters of the oscillatory ventilator were constant during whole measurement. We confirm a decrease of the amplitude of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 11 publications
0
5
0
Order By: Relevance
“…However, due to the smaller timescales associated with the percussion or minibursts, the pressure is expected to attenuate in actual lung geometry, which will manifest as reduced alveolar pressure. The pressure attenuation phenomenon has been reported in many studies on HFV (Rožánek et al 2012, Smallwood et al 2016). Under similar PIP, the MAPs recorded by HFPV is much lower as compared to that of PCV due to the shape of the pressure waveform.…”
Section: Discussionmentioning
confidence: 78%
“…However, due to the smaller timescales associated with the percussion or minibursts, the pressure is expected to attenuate in actual lung geometry, which will manifest as reduced alveolar pressure. The pressure attenuation phenomenon has been reported in many studies on HFV (Rožánek et al 2012, Smallwood et al 2016). Under similar PIP, the MAPs recorded by HFPV is much lower as compared to that of PCV due to the shape of the pressure waveform.…”
Section: Discussionmentioning
confidence: 78%
“…The results of this study showed that during HFOV, it is possible to monitor changes in trend in respiratory system compliance by analysis of reactance. According to the models, even the very peripheral lung segment compliances propagated to the proximal value of the total respiratory system compliance [41]. We conducted an in vitro laboratory experiment using defined physical models of the respiratory system with various values of compliance and flow resistance.…”
Section: Discussionmentioning
confidence: 99%
“…As an independent method for confirmation of dynamic hyperinflation or hypoinflation existence, a chest X-ray was used during the measurements. As tidal volumes and pressure amplitudes in the alveolar space during HFOV are very small in comparison with conventional mechanical ventilation [ 25 , 26 , 27 , 28 ], the diaphragm do not move significantly during HFOV breathing cycles, and therefore there is no need for a synchronization of the X-ray imaging with a certain phase of the breathing cycle.…”
Section: Methodsmentioning
confidence: 99%